2008
DOI: 10.1039/b803293a
|View full text |Cite
|
Sign up to set email alerts
|

Light-actuated high pressure-resisting microvalve for on-chip flow control based on thermo-responsive nanostructured polymer

Abstract: A simple light-actuated microvalve using a quartz halogen illuminator with tungsten filament was introduced to manipulate flow path effectively in micro-total analysis systems, which reduces system complexity and the need for on-chip integration. The microvalve device in cyclic olefin copolymer (COC) microchip functions very well based on the thermo-responsive polymer, poly(N-isopropylacrylamide) (PNIPAAm), whose pressure-tolerance can be tuned by changing the mechanical strength of polymer monolith inside the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 55 publications
0
80
0
Order By: Relevance
“…In particular, valves made using photo-responsive gels are of great interest as functional materials within micro-fluidic systems since actuation can be controlled by simple light irradiation, without physical contact, offering improvements in versatility during manifold fabrication, and control of actuation [9,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, valves made using photo-responsive gels are of great interest as functional materials within micro-fluidic systems since actuation can be controlled by simple light irradiation, without physical contact, offering improvements in versatility during manifold fabrication, and control of actuation [9,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Potential replacement technologies include electrostatic [10], magnetic [11], torque generated [12], Braille pin [13], thermal [14,15] and shape memory alloy (SMA) [3] actuation.…”
Section: Component-level Developmentsmentioning
confidence: 99%
“…For example, phase change microvalves using ohmic resistors as heat sources have response times of minutes [14]. Replacing the phase change element with a thermo responsive polymer (poly(N-isopropylacrylamide)) and reducing the thermal mass of the responsive element (100 mm valve scale) decreased the response time to seconds [15]. Favorably, the pressure resistance of microvalves in COC was very high (1350 psi), and could be optimized by modifying the crosslinker and tetrahydrofuran composition; unfortunately, the quartz halogen lamp used for heating has a large area (diameter = 1.3 cm), which severely limits the scalability.…”
Section: Component-level Developmentsmentioning
confidence: 99%
“…18). In order to exploit the advantages of stimulation by light, infrared radiation sources and temperature-sensitive hydrogels have been used to fabricate high-pressure-resistant microvalves based on poly(N-isopropylacrylamide) (PNIPAAm) [118]. In their work, the authors found that the pressure tolerance of the gel can be tuned by choosing suitable amounts of monomer and crosslinker for the polymer monolith inside the microchannel.…”
Section: Photosensitive Phsmentioning
confidence: 99%